High performance grinding and advanced cutting tools - Jackson, Mark J. (SpringerBriefs in applied sciences and technology, 2013)
High Performance Grinding and Advanced Cutting Tools discusses the fundamentals and advances in high performance grinding processes, and provides a complete overview of newly-developing areas in the field. Topics covered are grinding tool formulation and structure, grinding wheel design and conditioning and applications using high performance grinding wheels. Also included are heat treatment strategies for grinding tools, using grinding tools for high speed applications, laser-based and diamond dressing techniques, high-efficiency deep grinding, VIPER grinding, and new grinding wheels